Pengaruh Pengalaman Kerja, Tingkat Pendidikan Dan Pelatihan Kerja Terhadap Kinerja Karyawan Dinas Kependudukan Dan Pencatatan Sipil Kota Malang - Sonia Kartikasari; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims the effect of work experience, level of education and job training on the performance of the employees of the Department of Population and Civil Registration of Malang City. The number of samples is 63 employees. The sampling technique used was total sampling. The method of data collection in this study used a questionnaire. The results showed that simultaneously work experience, level of education and job training had an effect on employee performance. Partially work experience, level of education and job training affect employee performance. Keywords: Employee Performance, Work Experience, Education Level, Work  Training.